Students’ Learning Strategy In Enriching Vocabulary: Natural Science And Social Science Department At Senior High School - Perpisa, Lili; Sesmiyanti; Sarah, Novita (Yayasan Pendidikan Tanggui Baimbaian, 2023)
This research aims to describe English Vocabulary Learning Strategies (VLS) and to find the strategies most frequently used by Natural Sciences (IPA) and Social Sciences (IPS) students. In this research, researchers used quantitative methods, where data was collected using questionnaire survey procedures. The population of this research was class The sample was taken randomly (Random sampling) with a science percentage of 10% and social studies 10% so that a total sample of 18 science students and 14 social studies students were taken as samples. The research results show that the most dominant type of strategy used by students majoring in science is Metacognitive Strategy (83.02%) and the least frequently used strategy is Memory Strategy: Encoding (58.98%). On the other hand, students in the Social Sciences Program mostly used the Dictionary Strategy (82.65%) and the Activation Strategy (48.93%) was the least used strategy.